Efficacy of PECS block in addition to multimodal analgesia for postoperative pain management in patients undergoing outpatient elective breast surgery: A retrospective study - Uribe, Alberto A.; Weaver, Tristan E.; Echeverria-Villalobos, Marco; Periel, Luis; Pasek, Joshua; Fiorda-Diaz, Juan; Palettas, Marilly; Skoracki, Roman J.; Poteet, Stephen J.; Heard, Jarrett A. (Frontiers in Medicine, 2022)
Background: Pectoralis nerve blocks (PECS) have been shown in numerous studies to be a safe and effective method to treat postoperative pain and reduce postoperative opioid consumption after breast surgery. However, there are few publications evaluating the PECS block effectiveness in conjunction with multimodal analgesia (MMA) in outpatient breast surgery. This retrospective study aims to evaluate the efficacy of PECS’s blocks on perioperative pain management and opioid consumption. Methods: We conducted a retrospective study to assess the efficacy of preoperative PECS block in addition to preoperative MMA (oral acetaminophen and/or gabapentin) in reducing opioid consumption in adult female subjects undergoing outpatient elective breast surgery between 2015 and 2020. A total of 228 subjects were included in the study and divided in two groups: PECS block group (received PECS block + MMA) and control Group (received only MMA). The primary outcome was to compare postoperative opioid consumption between both groups. The secondary outcome was intergroup comparisons of the following: postoperative nausea and vomiting (PONV), incidence of rescue antiemetic medication, PACU non-opioid analgesic medication required, length of PACU stay and the incidence of 30-day postoperative complications between both groups. Results: Two hundred and twenty-eight subjects (n=228) were included in the study. A total of 174 subjects were allocated in the control group and 54 subjects were allocated in the PECS block group. Breast reduction and mastectomy/lumpectomy surgeries were the most commonly performed procedures (48% and 28%, respectively). The total amount of perioperative (intraoperative and PACU) MME was 27 [19, 38] in the control group and 28.5 [22, 38] in the PECS groups (p= 0.21). PACU opioid consumption was 14.3 [7, 24.5] MME for the control group and 17 [8, 23] MME (p = 0.732) for the PECS group. Lastly, the mean overall incidence of postsurgical complications at 30 days was 3% (N= 5), being wound infection, the only complication observed in the PECS groups (N=2), and hematoma (N=2) and wound dehiscence (N= 1) in the control group Conclusion: PECS block combined with MMA may not reduce intraoperative and/or PACU opioid consumption in patients undergoing outpatient elective breast surgery.